KONSEP SYURA MENURUT HAMKA DAN M. QURAISH SHIHAB - Saputro, Adfan Hari (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2016)
Abstract:This study is a library research using a philosophical approach and intended to examine how the concept of shura according to Hamka and M. Quraish Shihab’s view, which theygavein interpreting the verses of the Qur’an about shura in Tafsir al-Azhar and Tafsir al-Mishbah. This research will also examine the relevance of the interpretation of Hamka and M. Quraish Shihab about the shura concept in the present context.Based on the research results, Hamka and M. Quraish Shihab assume that shura can be changed to adjust the condition of society. This is consistent with the interpretation of contemporary exegetes. This definition is not conflicting with the interpretation of the classical commentators. However, M. Quraish Shihab then states that it doesn’t need to bind themselves to the verdict of Islamic scholars and even former friends, so causing confusion to think, because there is no clear frame for the detachment. In short, the interpretation of M. Quraish Shihab stained the relativism interpretation. Nevertheless, Hamka’s concept of shura is still in accordance with the interpretation of the commentators so it’s very relevant when it is applied in enforcing the principle of shura in society and the Islamic state. The efforts of some Muslims who build Islam through democracy,for example in Public Election, it does not mean that they recognize democracy as a part of Islam, but it just the way(wasîlah) in maintaining dharûratul khamsah Muslims to consider the serious benefits and harms.Keywords: shura; democracy; Hamka, Quraish Shihab.